The moth keeper ebook A graphic novel. - O'Neill, K. (2023)
Being a Moth Keeper is a huge responsibility and a great honor, but what happens when the new Moth Keeper decides to take a break from the moon and see the sun for the first time? From the author of the beloved Tea Dragon Society comes a must-read for fans of the rich fantasies of Hayao Miyazaki and the magical adventures of Witch Hat Atelier . Anya is finally a Moth Keeper, the protector of the lunar moths that allow the Night-Lily flower to bloom once a year. Her village needs the flower to continue thriving and Anya is excited to prove her worth and show her thanks to her friends with her actions, but what happens when being a Moth Keeper isn’t exactly what Anya thought it would be? Night after night, it is lonely in the desert, with only one lantern for light. Still, Anya is eager to prove her worth, to show her thanks to her friends and her village. But is it worth the cost? And yet something isn’t right. When Anya glimpses the one thing that could destroy what she’s meant to protect, her village and the lunar moths are left to deal with the consequences. K. O’Neill brings to life a beautifully illustrated fantasy with lush, gorgeous art and intricate world-building. A story about coming of age and community, The Moth Keeper is filled with magic, hope, and friendship. “Expressing quiet resilience, this story lifts up nature’s symbiotic relationships and the power of community.” – Kirkus Reviews , starred review